Comparison Of Factors That Influence The Stress Level Of Nurses In The ICU And ER At RSUD Toto Kabila - Alvin Akbar Thaib; Sabirin B. Syukur; Hartati Inaku (CV. AFDIFAL MAJU BERKAH, 2026)
Work stress among nurses is a critical issue that may reduce the quality of nursing care, particulary in high-intensity units such as the Intensive Care Unit (ICU) and Emergency Departement (ED). This Study aimed to compare nurses work stress levels in the ICU and ED and to analyze the influencing factors, including workload, social support and length of employment. This study employed a descriptive analytic design with a cross-sectional approach. The sample consisted of 48 nurses, including 20 ICU nurses and 28 ED nurses, selected using total sampling. Data were collacted using structured questionnaires and analyzed using Spearman Rank Correlation and Mann-Whitney U tests with a significance level of p<0.05. The results showed significant differences in work stress levels (p=0.003) and workload (p=0.004) between ICU and ED nurses. Workload had a strong positive correlation with work stress in ICU nurses (r=0.642; p=0.001) and ED nurses (r=0.711; p=0.000). Social support showed a significant negative correlation with work stress among ICU nurses (r= -0.402; p=0.045)., but not among ED nurses. Length of employment was not significantly associated with work stress in both units. Workload is the dominant factor affecting nurses work stress, particularly in the Emergency Department. Optimizing workload management and strengthening social support are essential to reduce nurses work stress.